Adapting to climate change: Exploring tourism vulnerability and agricultural development in Gedangan Village - Antriyandarti, Ernoiz; Ardila, Insyirah Ayu; Syarif, Jadid Ardian; Agustin, Laily; Cahyani, Latidah Dita; Panemuan, Rizki Guntur; Nugroho, Sasmito Agung (Institute of Advance Science, Social, and Sustainable Future, 2024)
Background: Researchers agree on the necessity of a robust framework to adapt to and mitigate climate change, encompassing environmental education, financial support, green tourism, eco-tourism, and conservation projects. This paper investigates the vulnerability of tourism to climate change, tourism under various climate scenarios, and adaptation strategies within this sector. The tourism industry’s reliance on energy sources such as water, electricity, and fossil fuels underscores the need for a thorough evaluation of systems and frameworks to ensure sustainability and resilience. Gedangan Village, located 14 km west of Boyolali's town center, is a major vegetable-producing area in Cepogo District, Central Java, Indonesia, characterized by its productive highland agriculture. Method: This study uses a descriptive-analytical method with a qualitative approach, focusing on a case study in Gedangan Village to understand its potential, issues, and transformations. The location was purposively selected due to its relevance, and data was collected through purposive sampling of key informants. The paper employs a literature review to support its findings, leveraging various databases and sources. Conclusion: The conclusion highlights the need for enhancing technological use and human resources to maximize Gedangan's agricultural potential and address the challenges posed by climate change.